Pedagogical Practices in Teaching SiSwati as a First Language in Diverse Linguistic Settings - Mngometulu, Tholakele Constance; Makgabo, Connie (Journal of Languages and Language Teaching, 2023)
This article reports on pedagogical practices in teaching SiSwati as a first language (SL1) in diverse linguistic settings of Eswatini. In response to educational research indicating the vital role played by a learner’s first language in learning, the Eswatini government embarked on an exercise of decolonising the curriculum in 2011 by using SiSwati as the medium of instruction and learning in the foundation and middle phases and a core subject throughout primary and senior secondary school. However, arguably, research on African language pedagogy is scanty, let alone teaching of SiSwati, as the little available research has been on issues of policy, thus leaving a knowledge gap on the pedagogy in SiSwati first language (SL1). Therefore, the purpose of this study is to explore pedagogical practices that are used in the SL1 class in compliance with the policy, which provides for SiSwati to be a compulsory subject and a vehicle for teaching and learning in early primary schools.. This qualitative case study involved eight teachers who taught SL1 in the foundation and middle phases. Data were generated through interviews. The findings indicated that teachers’ practices were anchored in the understanding that teaching SL1 meant equipping learners with functional language skills, such as productive and receptive skills, essential for studying across subject curricula. However,  a lack of pedagogical knowledge thwarted teachers’ practices to teach language in general, let alone to multilingual learners as expository pedagogy dominated SL1 classrooms, as opposed to curriculum requirements that learner-centred pedagogies anchored in social practice be used. Besides, these findings advocate for culturally responsive pedagogies appropriate to teach SL1 to learners from diverse linguistic backgrounds.